Pengaruh Efektifitas Penerapan Kartu Tani terhadap Penyaluran Pupuk Bersubsidi (Studi Kasus di Kabupaten Kepulauan Aru) - Enrico. M Lamidja; Wardis Girsang; Jeter D Siwalette (Ideas Publishing, 2023)
In an effort to facilitate access and affordable fertilizer prices for farmers, the Government has issued a number of regulations. The aim of this research is to find out how effective the application of farmer cards is in distributing subsidized fertilizer to farmers. Primary data was collected from farmers, fertilizer retailers and also stakeholders of the Tani Card Program in Aru Islands Regency, Maluku. Research sampling was carried out using a random sampling technique of 100 samples from all representatives in the Pulau-Pulau Aru sub-district. Research data was analyzed using quantitative descriptive methods with the Partial Least Square (PLS) method. The results of this research are that the effectiveness of implementing the farmer's card is not completely effective because it is hampered by several very basic factors so that the effectiveness of the farmer's card is quite low. The results of the research recommend that Stakeholders need to further improve coordination, especially in the process of planning subsidized fertilizer needs, the distribution process and monitoring the realization of subsidized fertilizer distribution.